2002
DOI: 10.1108/08876040210433211
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic benchmarking of hotel service quality

Abstract: Total customer satisfaction is one of the most important strategic weapons of best‐practice hotel organizations. However, hotel organizations cannot achieve total customer satisfaction without gaining the knowledge of a hotel’s competitive position in the changing marketplace and realizing the opportunity of continuous service improvement. With this in mind, this paper develops a set of service benchmarks that help hotel managers monitor their service delivery process, identify performance gaps, and take corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 11 publications
2
83
0
Order By: Relevance
“…Therefore, Kessler (1996) stated that ensuring a high level of service from the frontline employees should be included in the hotels' management strategy. By doing so, a hotel should achieve the customer satisfaction logically.According to Min et al (2002), cleanliness of a guest room is the most significant feature in forming perceptions of hotel service quality; as well as courtesy of employees, quietness of a guest room, handling of complainants and the level of comfort of bedding. Compared to Min and Min (1996), the level of importance of the cleanliness stayed the same, while the level of importance of courtesy of employees and handling of complaints declined dramatically.…”
mentioning
confidence: 99%
“…Therefore, Kessler (1996) stated that ensuring a high level of service from the frontline employees should be included in the hotels' management strategy. By doing so, a hotel should achieve the customer satisfaction logically.According to Min et al (2002), cleanliness of a guest room is the most significant feature in forming perceptions of hotel service quality; as well as courtesy of employees, quietness of a guest room, handling of complainants and the level of comfort of bedding. Compared to Min and Min (1996), the level of importance of the cleanliness stayed the same, while the level of importance of courtesy of employees and handling of complaints declined dramatically.…”
mentioning
confidence: 99%
“…According to a study by Lewis and McCann [41] on failed services of hotels, business and leisure travellers think dirty rooms are the worst problem of all. Min et al suggest that room neatness is the most important factor perceived by customers [7]. Tsang and Qu argue that there is a gap, statistically significant, between their expectations and the perception of room neatness [9].…”
Section: Discussionmentioning
confidence: 99%
“…They are 1) room values: cleanness, comfort, atmosphere, toiletry, prices, space and giveaways; 2) front-desk services: manner, real-timeliness, complaint processing, reservation, reception, leisure activities and relevant guidance and services. Min et al perform a dynamic benchmarking of service quality of the hotel industry and divide service quality characteristics into two categories with a total of 20 items [7]. The additional items for room values are quietness, desk facilities, Internet, faxing and free local calls.…”
Section: Service Quality Of Hotel Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Many benchmarking processes in e-commerce have been reported for instance Ahmed et al (2006) demonstrated global benchmarking for internet and ecommerce applications and Rickards (2007) evaluated the benchmarking's for the development for an e-commerce in small and medium enterprise. Apart from this, many researchers have also utilized various techniques in benchmarking for instance AHP has been successfully utilised for benchmarking in process performance (Frei & Harker, 1999), strategic performance (Partovi, 2001), quality performance (Min & Chung, 2002) and logistics performance of the postal industry (Chan et al, 2006). This study aimed elucidate the factors that affect success in on-line retail service and then evaluate and rate these factors by analyzing components using the Fuzzy Analytic Hierarchy Process (FAHP) and to benchmark the performance or rank the present case company based on critical success factors among its competitors using Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method.…”
Section: Introductionmentioning
confidence: 99%